Direção espiritual na TV canção nova: análise do discurso do Padre Fábio de Melo - Andrade, Débora Cristina Diógenes (2009)
The aim of the research is to analyze Direção Espiritual a TV program produced by Catholic Church and presented by Canção Nova Channel. The program is presented by Father Fábio de Melo, a catholic priest that also is a famous religious singer and writer. The analyses included not only some TV programs, but also interviews with some of the viewers and Fabio de Melo himself. The results points out the emergence in Brazil of a new religious speech from Catholic Church founded in comprehension path, dissociated from punishment and guilty. This religious speech is more like a self help speech rather than a tradicional religious discourse itself, very similar to psychotherapeutic speech. The TV program presented by Fabio de Melo is guided in tiny line of sacre and profane which announces contradictions but also a new blend of religious approach in contemporary days